SARS-CoV-2 mRNA Vaccine Effectiveness in Health Care Workers by Dosing Interval and Time Since Vaccination: Test-Negative Design, British Columbia, Canada. (15th April 2022) - El Adam, Shiraz; Zou, Macy; Kim, Shinhye; Henry, Bonnie; Krajden, Mel; Skowronski, Danuta M
Abstract: Background: One- and two-dose mRNA vaccine effectiveness (VE) estimates against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection by dosing interval and time since vaccination were assessed among healthcare workers (HCWs) in publicly funded acute and community (nonresidential) healthcare facilities in British Columbia, Canada. Methods: A test-negative design was used with controls matched to cases (6:1) on epidemiological week of SARS-CoV-2 test date. mRNA vaccination was defined by receipt of the first dose ≥21 days or second dose ≥14 days before the test date. HCWs ≥18 years old tested for SARS-CoV-2 between epi-weeks 3 and 39 (January 17–October 2, 2021) were included, when varying dosing intervals and a mix of circulating variants of concern contributed, including Delta dominance provincially from epi-week 31 (August 1). Results: Single- and two-dose analyses included 1265 and 1246 cases, respectively. The median follow-up period (interquartile range) was 49 (34–69) days for single-dose and 89 (61–123) days for two-dose recipients, with 12%, 31%, and 58% of second doses given 3–5, 6, or ≥7 weeks after the first. Adjusted mRNA VE against SARS-CoV-2 was 71% (95% CI, 66%–76%) for one dose and 90% (95% CI, 88%–92%) for two doses, similar to two heterologous mRNA doses (92%; 95% CI, 86%–95%). Two-dose VE remained >80% at ≥28 weeks post–second dose. Two-dose VE was consistently 5%–7% higher with a ≥7-week vs 3–5-week interval between doses, but with overlapping confidence intervals. Conclusions: Among HCWs, we report substantial single-dose and strong and sustained two-dose mRNA vaccine protection, with the latter maintained for at least 7 months. These findings support a longer interval between doses, with global health and equity implications.